2011
DOI: 10.1007/s11552-011-9379-8
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship in Surgical Training: A Systematic Review

Abstract: Objective This review systematically examines the literature regarding mentor-mentee relationships in surgery. Background The usefulness of mentorship in surgical training has been expressed in many articles. However, to date, there has been no systematic review on mentoring surgical trainees. This surgical environment is different from other areas of medicine and requires young surgeons to learn skills not readily available from textbooks. Instead, mentors are a valuable mode of transferring this knowledge to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 43 publications
1
107
1
3
Order By: Relevance
“…Surgery: Three surgical reviews described use of formal mentoring approaches [17,27,32]. Healy et al reported that residents preferred formal mentoring approaches given its structured approach, the availability of trained mentors and the presence of clear mentoring objectives [17].…”
Section: Formal Mentoring Approachmentioning
confidence: 99%
“…Surgery: Three surgical reviews described use of formal mentoring approaches [17,27,32]. Healy et al reported that residents preferred formal mentoring approaches given its structured approach, the availability of trained mentors and the presence of clear mentoring objectives [17].…”
Section: Formal Mentoring Approachmentioning
confidence: 99%
“…Other factors associated with having a mentor include increased (professional or personal?) support (31), increased publication rate (32), status in the medical community (32), empowerment, a sense of community (11), and increased visibility (33).…”
Section: What Are the Advantages Of Having A Mentor?mentioning
confidence: 99%
“…Barriers to advancement include lack of mentorship (34), difficulty in networking (6), time constraints (32), and ineffective mentoring (17). Consistently, only about half of survey respondents report having a formal mentor program (3,18,32) or having a mentor at all (14).…”
Section: "Barriers" To Finding Mentors For Both Gendersmentioning
confidence: 99%
See 2 more Smart Citations